Case report: Chronic granulomatous disease presenting with early-onset inflammatory bowel disease and normal oxidative burst testing - Sanjib Mondal; Pandiarajan Vignesh; Sathish Kumar Loganathan; Kanika Arora; Jhumki Das; Amit Rawat; Surjit Singh (Frontiers Media S.A., 2023)
BackgroundDue to the lack of widespread availability of flow cytometry services for immunodeficiency, nitroblue tetrazolium test (NBT) is the commonly used screening modality to identify patients with chronic granulomatous disease (CGD) in developing countries.ProcedureWe report a child with X-linked CGD with residual NADPH oxidase activity who had an indeterminate NBT result even in the presence of classical manifestations of CGD.ResultsA 7-year-old boy presented with recurrent episodes of inflammatory colitis and Burkholderia cepacia septicaemia at the age of 3 years. He also had cervical adenitis due to Mycobacterium tuberculosis. NBT performed on multiple occasions was not suggestive of CGD. Dihydrorhodamine (DHR) test using phorbol myristate acetate (PMA) as a stimulant revealed a small blunt peak suggestive of AR-CGD; however, significant reduction in NADPH oxidase activity was noted with milder stimulants such as Escherichia coli and Staphylococcus aureus. Genetic analysis revealed a hemizygous pathogenic variant in CYBB. Flow cytometry showed diminished gp91phox expression in the patient's neutrophils suggestive of X-linked CGD.ConclusionOur case highlights that early-onset inflammatory bowel disease can be a presenting manifestation of CGD and diagnosis of CGD can be missed if NBT alone is used for screening, especially in the presence of NADPH oxidase activity. Diagnosis of "CGD with residual NADPH oxidase activity" requires a high degree of clinical suspicion, and performing DHR with different stimulants can unravel the diagnosis.